2009
DOI: 10.18388/abp.2009_2509
|View full text |Cite
|
Sign up to set email alerts
|

Full length genome sequence of Polish isolate of Beet soil-borne virus confirms low level of genetic diversity.

Abstract: The complete nucleotide sequence of a Polish isolate of Beet soil-borne virus was determined for the first time. The genome organization was identical with those previously established for isolates from Germany and China. A comparison of the Polish isolate with others deposited in GenBank revealed high level of nucleotide identity, about 98-100%, throughout the genome analyzed. The ratio between non-synonymous and synonymous substitutions was rather low suggesting a negative selective pressure. The non-synonym… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 15 publications
2
4
0
Order By: Relevance
“…This finding is in line with that of other studies ( Borodynko et al, 2009 ; Koenig et al, 2000 ; Wang et al, 2008 ). Consistent with previous studies ( Borodynko et al, 2009 ; Wang et al, 2008 ), our results revealed that TGB3 (Pi = 0.034) was a more variable gene region than TGB1 and TGB2. Sequence diversity in the 5′-UTRs and 3′-UTRs of RNA1 and RNA3 were relatively higher than those of RNA2 ( Supplementary Table 1 ).…”
Section: Resultssupporting
confidence: 94%
See 4 more Smart Citations
“…This finding is in line with that of other studies ( Borodynko et al, 2009 ; Koenig et al, 2000 ; Wang et al, 2008 ). Consistent with previous studies ( Borodynko et al, 2009 ; Wang et al, 2008 ), our results revealed that TGB3 (Pi = 0.034) was a more variable gene region than TGB1 and TGB2. Sequence diversity in the 5′-UTRs and 3′-UTRs of RNA1 and RNA3 were relatively higher than those of RNA2 ( Supplementary Table 1 ).…”
Section: Resultssupporting
confidence: 94%
“…MN087414, MN087415, and MN087416 for RNAs 1, 2, and 3, respectively) were determined. The genome organization and base composition of both isolates were similar to other BSBV isolates ( Borodynko et al, 2009 ; Camelo-Garcia et al, 2019 ; Crutzen et al, 2009 ; Koenig and Loss, 1997 ; Koenig et al, 1996 , 1997 ; Wang et al, 2008 ).…”
Section: Resultssupporting
confidence: 55%
See 3 more Smart Citations